FEASIBILITY ANALYSIS OF A BATCHING PLANT INVESTMENT FOR THE KEDIRI-TULUNGAGUNG TOLL ROAD PROJECT - Suwito, Suwito; Nugroho, Laksono Djoko; Muhammadun, Haris (International Journal of Social Service and Research, 2025)
This study evaluates the feasibility of establishing a batching plant for the Kediri-Tulungagung toll road construction, specifically for the Dhoho Kediris Airport toll access, section 2. Observations were conducted with key stakeholders at the project site, including concrete production costs, operational schedules, and potential bottlenecks. The data was analyzed using a quantitative approach with statistical software, focusing on investment feasibility indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (Rohman & Husin, 2024). The results of the analysis show that the NPV is IDR5,599,938,029.34 with IRR reaching 82.71%, far above the Minimum Attractive Ratio (MARR) of 12%. In addition, the efficiency of concrete distribution time to the site improved daily work productivity. This study provides critical insights into the logistical, economic, and operational aspects of setting up a batchesing plant, which is essential for ensuring the efficient production of concrete required for the construction project. The findings can serve as a valuable reference for future projects in similar contexts, enhancing the planning and execution of toll roads in Indonesia.